(untitled) (Journal on Geoinformatics, Nepal, 2024)
Increase in population and its migration towards urban areas are leading to unmanaged urbanization generating pressure on the land. To meet the demand of migrating people, high rise buildings are being developed. Since land is a limited resource, this is a better solution. Rights on vertical strata in the same parcel need to be recorded technically and legally in cadastral data as well as land registers. In Nepali context, despite some limited legal provisions for recording 3D cadastral data, there is still a gap in recording spatial information technically. On the other hand, due to the lack of clear spatial information recording and limited provisions for recording in land registers, land disputes are also arising. However, an increase in land dispute cases is not the only issue; there are a huge number of reasons related to legal and technical provisions in land administration. Therefore, in order to minimize land dispute cases, 4D cadastre can provide a better solution. The paper discusses the legal provisions of 3D cadastre and its need in the context of Nepal, along with the need for 4D cadastre to support in reducing land dispute cases.